Advances in the Security Features of SATA Solid State Drives - Balaso Jagdale (Advanced Aspects of Engineering Research Vol. 16, 2021)
This chapter focuses on advanced experiments and improvements in the security features of the SATA solid-state drives. In modern computer applications, the quantity of data is growing day by day, and accordingly, the size of storage media is also increasing rapidly. Flash memories are used in most storage devices, one of which is a Solid State drive. Solid-state drives, or SSDs, are non-volatile data storage devices that store data in NAND or NOR flash memories, providing features similar to traditional hard disk drives (HDD). This chapter provides a comparative study of Solid-state drives over Hard-disk drives. Further, a technique is designed and implemented to enhance SATA Solid-state drives security features in terms of user authentication, access control, and media recovery from the ATA security feature set.